Implementasi Manajemen Oleh Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SMK Negeri 1 Siborongborong - Suarnita Zai; Senida Harefa; Abai Manupak Tambunan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The aim of this research is to understand how the principal's management is implemented in improving the quality of education at SMK Negeri 1 Siborongborong. The type of research used in this research is a qualitative descriptive research method using observation, interview and documentation techniques. The main subject of this research is the school principal and the sources of information supporting this research are teaching and educational staff, committees and students. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The findings of this research found that the implementation of school principal management to improve the quality of education at SMK Negeri 1 Siborongborong was through planning and preparing work plans as well as preparing the school's vision, mission and goals. Furthermore, the school principal's efforts to improve the quality of education are carried out, such as grouping the tasks of each teacher and employee according to their abilities and expertise. Apart from that, in carrying out the process of improving the quality of education, the principal mobilizes the resources available at the school by providing encouragement and motivation in implementing each activity. Finally, in terms of achieving educational quality, school principals routinely carry out evaluation activities and make improvements so that the quality of education becomes better. Therefore, school principal management in improving the quality of education can support the realization of eight national education standards, namely content standards, process standards, graduate competency standards, teacher and teaching staff standards, facility and infrastructure standards, and management standards. standards, financing criteria and evaluation criteria, educate.